Sex-Based Variations in Hemato-Physiological Characteristics of Patients with Major Depressive Disorder: Clinical and Socioeconomic Insights - Basim A. Abd; Hayder Abdul-Amir Makki Al-Hindy; Samer Raheem Obaid (Medical Journal of Babylon)
Background: Major depressive disorder (MDD) is a well-known psychiatric condition that can affect a diverse range of populations worldwide. Objectives: This research aimed to examine sex differences in hemato-physiological, clinical, and socioeconomic factors, as well as response to antidepressant psychiatric therapy, in a group of 198 adult subjects with MDD. Materials and Methods: The study collected basic demographic characteristics, including age, leukocyte counts, body mass index (BMI), hemoglobin (Hb) blood values, and inflammatory marker “C-reactive protein” (CRP). The cohort exhibited significant alterations between the two sexes in various clinical variables. Results: Despite females exhibiting high levels of somatic symptomatology, as evidenced by increased white blood cell counts and BMI, male patients presented higher Hb readings, reflecting probable disparities in physical body responses to depression. A comprehensive review of marital status and educational attainment revealed further sex-linked changes in MDD manifestation. The findings suggest that female patients with higher educational attainment exhibited higher BMI measures compared to their male counterparts, highlighting latent sociocultural impacts on disease presentation. Moreover, marital status meaningfully impacted the clinical presentation of both sexes. The age and BMI physical measurements of married individuals differed from those who were non-married. Additionally, the socioeconomic setting affects the clinical performances of MDD patients. The fluctuating BMI means of those residing in urban and rural areas underscore the significance of external inspirations on health outcomes. Furthermore, the administration of antidepressant medicines revealed sex-associated differences in clinical body reactions, predominantly in CRP serum levels, indicating potential alterations in the effectiveness of antidepressants between the two sexes. Conclusion: The present work focuses on the challenges in classifying and managing depressive symptoms, highlighting the importance of considering sex-specific alterations. Considering such variations might indeed help improve therapy plans and improve their outcomes. Given the complexity of MDD, medications should be modified to the individual’s clinical symptomatology, sex, and socioeconomic circumstances.